Continuity and Change? Reading Young Adult Literature Through a Technology‐Focused Critical Lens. Issue 6 (4th April 2021) - Glazer, Jeremy; Seglem, Robyn; Garcia, Antero
Abstract: This article offers a way to leverage young adult literature in guiding students to consider the meanings of continuity and change within their own development. Borrowing theories of change from the evolutionary sciences, we developed a critical lens focusing on the role of technology in young adult literature. Based on a comprehensive review of Michael L. Printz Award and Honor titles and YALSA Teens' Top Ten books from the past two decades, we identified how two theories of evolution, gradualism and punctuated equilibrium, offer a frame for interpreting young adult literature. Through an examination of the novels Asking for It by Louise O'Neill and Butter by Erin Jade Lange, we demonstrate how these theories can be used in the language arts classroom to enhance discussions about change brought on by technology to provoke deep, intertextual readings of young adult literature.